Aerial sonic anemometry for wind resource assessment - Ribeiro, Luís Frölén (2014)
This project intends to recur to sonic anemometers in a airborne platforms to get wind information over the flying area between met masts or waypoints. Multiple platforms measuring simultaneously to complement ground based measurements. The concept is being tested and preliminary results show that key issues are related to the positioning system – differential GPS and autopilot.